2015
DOI: 10.1017/jfm.2015.385
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity effects on nonlinear wave–current interactions in deep water

Abstract: The effects of uniform vorticity on a train of 'gentle' and 'steep' deep-water waves interacting with underlying flows are investigated through a fully nonlinear boundary integral method. It is shown that wave blocking and breaking can be more prominent depending on the magnitude and direction of the shear flow. Reflection continues to occur when sufficiently strong adverse currents are imposed on 'gentle' deep-water waves, though now affected by vorticity. For increasingly positive values of vorticity, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It should be noted that, although the waves of interest are irrotational even for Ω = 0, in this paper, only the waves without a shear current are referred to as irrotational waves (Ω = 0). On the basis of this formulation, the full Euler system has been numerically solved by Simmen & Saffman (1985), Teles da Silva & Peregrine (1988) and Vanden-Broeck (1996) for steady waves, and by Choi (2009) and Moreira & Chacaltana (2015) for unsteady waves. It has been known that the limiting form of steady waves of symmetric profile can have a corner at the wave crest with an inner angle of 120 • which is independent of the shear strength Ω (Milne-Thomson 1968, p. 403, §14.50), similarly to the case of irrotational waves (Ω = 0).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, although the waves of interest are irrotational even for Ω = 0, in this paper, only the waves without a shear current are referred to as irrotational waves (Ω = 0). On the basis of this formulation, the full Euler system has been numerically solved by Simmen & Saffman (1985), Teles da Silva & Peregrine (1988) and Vanden-Broeck (1996) for steady waves, and by Choi (2009) and Moreira & Chacaltana (2015) for unsteady waves. It has been known that the limiting form of steady waves of symmetric profile can have a corner at the wave crest with an inner angle of 120 • which is independent of the shear strength Ω (Milne-Thomson 1968, p. 403, §14.50), similarly to the case of irrotational waves (Ω = 0).…”
Section: Introductionmentioning
confidence: 99%
“…Key nonlinear treatments are those of Simmen and Saffman () and Teles da Silva and Peregrine (). Of particular interest is the numerical scheme for fully nonlinear stationary and solitary waves on arbitrary 2D shear currents due to Dalrymple (), and followed by further numerical work on this question (Ko & Strauss, ; Moreira & Chacaltana, ; Nwogu, ). The present effort is restricted to linear waves; a comparison of the effect on wave speed of shear versus that of nonlinearity is an important topic for the future; refer to Swan and James () for some results up to second order in wave steepness.…”
Section: Introductionmentioning
confidence: 99%
“…For a review on the recent rigorous results, the reader can refer to Constantin & Varvaruca (2011) and Kozlov & Kuznetsov (2014). Among the authors using asymptotic methods or purely numerical methods, on can cite Tsao (1959), Dalrymple (1974), Brevik (1979), Simmen & Saffman (1985), Teles da Silva & Peregrine (1988) , Kishida & Sobey (1988), Vanden-Broeck (1996), Swan & James (2001), Ko & Strauss (2008), Pak & Chow (2009), Cheng, Cang & Liao (2009 , Moreira & Chacaltana (2015), Hsu, Francius, Montalvo & Kharif (2016), Ribeiro-Jr, Milewski & Nachbin (2017). Although the recent important theoretical developments have confirmed that periodic waves can exist over flows with arbitrary vorticity, it appears that their stability to infinitesimal disturbances and their subsequent nonlinear evolution have not been studied extensively so far.…”
Section: Introductionmentioning
confidence: 99%